Urgensi Olah Tempat Kejadian Perkara Dalam Proses Pembuktian - Muhammad Jasman; Patahillah Asba; Iswandy Rani Saputra (Jurnal Litigasi Amsir, 2023)
This research was carried out with the aim of carrying out the collection of evidence at the crime scene in the investigation process and finding out the function of the crime scene (TKP) in the investigation. The type of research used in this research is normative and empirical research or what is usually legal research which combines the two. The results of the study show that evidence and evidence are very important for the investigation process carried out by the Pinrang Police investigators. Evidence and evidence can usually be found at the crime scene. The implementation of the collection of evidence and evidence at the crime scene carried out by the Semarang Polrestabes was in accordance with the procedures and regulations currently in force. As well as the function of processing the scene of a case in an investigation is to determine whether an event suspected of being a crime is a crime or not; clarify who is the perpetrator of the crime that occurred; and seek and collect evidence at the scene of the incident for the benefit of further investigation.